PERTUNJUKAN KESENIAN TRADISI DALAM ACARA BAKAUA DI NAGARI KOTO TUO KABUPATEN SIJUNJUNG - Marshella Saskia Bonita; Wimbrayardi (Universitas Negeri Padang, 2026)
This study aims to describe the forms of performances and arts presented in the series of Bakaua traditional events in Nagari Koto Tuo. The type of research is qualitative with a descriptive analytical method. The research instrument is the researcher themselves, assisted by stationery, a camera and a voice recorder. Data was collected through literature study, observation, interviews and documentation. The steps of data analysis are data collection, data reduction and drawing or verifying conclusions. The results of the study show that Bakaua is a customary tradition that is still maintained as a form of the community's gratitude to Allah SWT for the harvest and to strengthen social togetherness. This tradition is rooted in the life of agrarian communities and is carried out through structured stages, beginning with a deliberation by the niniak mamak, the opening of customs through the pasambahan speech, collective prayers, the delivery of customary advice, and finally the shared meal of bajamba as a symbol of community solidarity. In addition to the customary and religious proceedings, Bakaua is also complemented by elements of traditional arts such as the pasambahan dance, plate dance, silek, randai, accompanied by talempong and gandang music. The presence of these arts shows that Bakaua functions not only as a customary ceremony but also as a medium for cultural preservation and strengthening the identity of the Nagari Koto Tuo community. Thus, the Bakaua tradition holds significant social, cultural, and spiritual values in maintaining the continuity of Minangkabau customs amidst the developments of the times.